GAMBARAN EFEK SAMPING OBAT KEMOTERAPI PADA PASIEN KANKER PAYUDARA DI RSUP DR. SARDJITO YOGYAKARTA PERIODE TAHUN 2012 - , OKKY KURNIAWAN; , Dra. Tri Murti Andayani, Sp.FRS, Ph.D., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Breast cancer is a common disease among women with the greatest risk of death.Treatment of breast cancer has nearly most of the side effects,but the rate of occurrence of adverse effects of drugs are not always arise because the goals are not enough drugs that act selectively on the target action.The purpose of this study to describe the side effects of breast cancer chemotherapy. Non-experimental study with data collected retrospectively from the patient's medical record.Subjects were breast cancer patients Hospital Dr. Sardjito who met the inclusion criteria with a primary diagnosis of breast cancer who received chemotherapy drug therapy during the period in 2012.The data obtained were analyzed descriptively that aims to provide a description of the study subjects. Patterns of drug use in breast cancer patients undergoing chemotherapy hospitalized in the department of breast cancer Dr.Sardjito period in 2012, from 40 patients with 105 episodes,CAF chemotherapy regimen consisting of cyclophosphamide, doxorubicin, flourouracil is the most chemotherapy regimens are given for 43 episodes (40.95%).Potential side effects in the treatment of breast cancer that is equal to 58 episodes (55.23%).Side effects that often occur in patients during treatment is the side effects of nausea by 32 cases.The characteristics of each of the side effects of chemotherapy regimens: CAF (cyclophosphamide, doxorubicin, flourouracil) & AT (doxorubucin, paclitaxel) nausea